Partners in Crime: Diffusion of Responsibility in Antisocial Behaviors - Sascha Behnk; Li Hao; Ernesto Reuben (Institute of Labor Economics (IZA), 2017)
Using a series of sender-receiver games, we find that two senders acting together are willing to behave more antisocially towards the receiver than single senders. This result is robust in two contexts: when antisocial messages are dishonest and when they are honest but unfavorable. Our results suggest that diffusion of responsibility is the primary reason for the increased antisocial behavior as our experimental design eliminates competing explanations. With a partner in crime, senders think that behaving antisocially is more acceptable and experience less guilt. Importantly, we identify a crucial condition for the increased antisocial behavior by groups: the partner in crime must actively participate in the decision-making. Our results have important implications for institutional design and promoting prosocial behaviors.
Keywords: D70; D91; C92; D63; 330; diffusion of responsibility; antisocial behavior; moral norms; guilt aversion